2018
DOI: 10.1093/annonc/mdy022
|View full text |Cite
|
Sign up to set email alerts
|

Neopepsee: accurate genome-level prediction of neoantigens by harnessing sequence and amino acid immunogenicity information

Abstract: Neopepsee can detect neoantigen candidates with less false positives and be used to determine the prognosis of the patient. We expect that retrieval of neoantigen sequences with Neopepsee will help advance research on next-generation cancer immunotherapies, predictive biomarkers, and personalized cancer vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 23 publications
0
116
0
Order By: Relevance
“…17 Neoantigen prediction can be exploited to identify responders to immune checkpoint inhibitors. 18,19 The purposes of this study were to characterize driver genes, mutational signatures and prognosticators in melanoma patients who were treated by ICB. [5][6][7][8][9][10] Findings emerged from this study may be useful for guiding immunotherapy treatment for melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…17 Neoantigen prediction can be exploited to identify responders to immune checkpoint inhibitors. 18,19 The purposes of this study were to characterize driver genes, mutational signatures and prognosticators in melanoma patients who were treated by ICB. [5][6][7][8][9][10] Findings emerged from this study may be useful for guiding immunotherapy treatment for melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increased interest in neoantigen-based therapeutic tumor vaccine therapy, prediction algorithms capable of directly predicting for neoantigen immunogenicity are lacking (50), and no neoantigen immunogenicity predictor trained specifically on tumor antigen data exists. Current neoantigen immunogenicity predictors are instead trained on databases containing immunogenicity scores from all potential MHC binding epitopes, of which the biology may not closely match that of mutation-derived tumor antigens.…”
Section: Discussionmentioning
confidence: 99%
“…However, peptides with a predicted high MHC I binding affinity are not necessarily immunogenic. In neoepitope prediction strategies, attempts such as the integration of information concerning the hydrophobicity of the TCR contact region [149,164], amino acid characteristics [140] or binding differences between wild-type and mutant epitopes [149] yield at increasing the probability to identify clinically relevant neoepitopes [149]. Calis et al reported two common properties of neopeptide-MHC combinations, which cause differences in T cell recognition: (1) the composition of amino acids in the position 4-6 of the presented peptide as well as (2) the size and absence/presence of aromatic side chains [140].…”
Section: Alterations In the Antigen Presenting Pathwaymentioning
confidence: 99%